Exosomal microRNAs derived from colon cancer cells promote tumor progression by suppressing fibroblast TP53 expression. Issue 8 (9th July 2019) - Yoshii, Shunsuke; Hayashi, Yoshito; Iijima, Hideki; Inoue, Takanori; Kimura, Keiichi; Sakatani, Akihiko; Nagai, Kengo; Fujinaga, Tetsuji; Hiyama, Satoshi; Kodama, Takahiro; Shinzaki, Shinichiro; Tsujii, Yoshiki; et al.
Abstract: The tumor microenvironment offers favorable conditions for tumor progression, and activated fibroblasts, known as cancer‐associated fibroblasts, play a pivotal role. TP53‐deficient cancer cells are known to induce strong fibroblast activation. We aimed to elucidate the oncogenic role of exosomes derived from TP53‐deficient colon cancer cells in fibroblast proliferation and tumor growth. Cancer cell‐derived exosomes (CDEs) were isolated from the conditioned media of cancer cells using a sequential ultracentrifugation method. The effects of exosomes on tumor growth were evaluated using human cell lines ( TP53 ‐WT colon cancer, HCT116; TP53 ‐mutant colon cancer, HT29; and fibroblasts, CCD‐18Co and WI‐38) and an immune‐deficient nude mouse xenograft model. HCT116 (HCT116 sh p53 ) cells deficient in TP53 accelerated cocultured fibroblast proliferation compared to TP53 ‐WT HCT116 (HCT116 sh control ) cells in vitro. Exosomes from HCT116 sh p53 cells suppressed TP53 expression of fibroblasts and promoted their proliferation. Xenografts of HCT116 sh p53 cells grew significantly faster than those of HCT116 sh control cells in the presence of co‐injected fibroblasts, but this difference was diminished by CDE inhibition. Microarray analysis identified upregulation of several microRNAs (miR‐1249‐5p, miR‐6737‐5p, and miR‐6819‐5p) in TP53‐deficient CDEs, which were functionally proven to suppress TP53 expression in fibroblasts. Exosomes derived from TP53 ‐mutant HT29 cells also suppressed TP53 expression in fibroblasts and accelerated their growth. The proliferative effect of HT29 on cocultured fibroblasts was diminished by inhibition of these miRNAs in fibroblasts. Our results suggest that CDEs play a pivotal role in tumor progression by fibroblast modification. Cancer cell‐derived exosomes might, therefore, represent a novel therapeutic target in colon cancer. Abstract : Exosomes derived from cancer cells play a pivotal role in tumor progression through fibroblast modification and might represent a novel therapeutic target in colon cancer.